2014
DOI: 10.1371/journal.pone.0085588
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum C-Reactive Protein Level Is Associated with Increased Storage Lower Urinary Tract Symptoms in Men with Benign Prostatic Hyperplasia

Abstract: ObjectiveChronic inflammation is considered as one of the contributing mechanisms of lower urinary tract symptoms (LUTS). Serum C-reactive protein (CRP) level is the widely used biomarker of inflammatory status. This study investigated the association between serum CRP level in men with benign prostatic hyperplasia (BPH) and lower urinary tract symptoms (LUTS) before and after medical treatment.MethodsA total of 853 men with BPH and LUTS were enrolled. All patients completed the International Prostate Symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
2
42
0
1
Order By: Relevance
“…However, they did not make any comment in these regards. Hung et al (1) identified this situation in their study, but they could not clarify this issue and could not assert any hypothesis. Only the determination of the situation was made in both articles.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…However, they did not make any comment in these regards. Hung et al (1) identified this situation in their study, but they could not clarify this issue and could not assert any hypothesis. Only the determination of the situation was made in both articles.…”
Section: Discussionmentioning
confidence: 79%
“…In their study, Hung et al (1) reported that serum CRP levels increase with age in the association of BPH and LUTS; besides, they identified a positive correlation between the filling symptoms and high LUTS values and the CRP. It may be asked though, why does CRP rise in patients with only high filling symptoms?…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations